High-voltage precursor material and preparation method thereof, positive electrode material, positive plate and lithium ion battery
Through the preparation method of oxidation and doping of high-voltage precursor material NixCoyMnzMw(OH)2, the problem of poor circulation performance of the positive electrode material at high voltage is solved, high capacity and excellent circulation performance are achieved, and ion mixing and irreversible phase are reduced. Changes improve the overall performance of the battery.
Patent Information
- Application Number
- CN202411491643.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-14
AI Technical Summary
The existing high-voltage ternary positive electrode materials become larger when the cycle times increase, the battery capacity decays quickly, the crystal structure stability is poor, and the ion mixing and irreversible phase change are prone to problems such as ion mixing and irreversible phase change, making it difficult to maintain excellent cycling performance under high voltage. .
Using the high-voltage precursor material NixCoyMnzMw(OH)2, prepared by oxidation and doping method, a, f, and e are controlled to satisfy 1000a-f≥15-e, and obtain internal loose and porous and external dense materials, doping element M Including Mg, Al, Ce, Mo, B and Ta, ensuring structural stability and high specific surface area.
The positive electrode material with good cycling performance at high voltage is achieved, which reduces the degree of ion mixing, reduces irreversible phase change, and improves the capacity and cycle stability of the battery, especially the performance under high temperature conditions.
Smart Images

Figure CN119306269A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a high voltage precursor material and a preparation method thereof, a positive electrode material, a positive electrode sheet and a lithium ion battery. Background Art
[0002] In recent years, the installed capacity of power batteries has continued to increase. For consumers, the core demands are driving range and fast charging speed, which requires the battery energy density to continue to increase. Therefore, demands such as high energy density, high safety, and low cost are driving the technological innovation of power batteries. The energy density of the positive electrode material will directly affect the overall performance of the power battery. Capacity and voltage together determine the energy density of the material. In order to achieve the improvement of energy density, the industry mainly improves the energy density of downstream power batteries by increasing the charging voltage of the material (high voltage) and increasing the nickel content (high nickel). The high voltage route increases the battery charging cut-off voltage so that the positive electrode material can release more lithium ions at a higher voltage, thereby increasing the capacity and operating voltage at the same time, thereby achieving the purpose of increasing energy density.
[0003] At present, the basic route for high voltage is based on medium-nickel ternary materials, which are superior to high-nickel ternary materials in terms of raw materials, production processes, and processing costs. At the same time, since the nickel content of high-voltage materials is relatively low and the production process is not as complicated as high-nickel ternary materials, high-voltage positive electrode materials have certain safety improvements while improving energy density.
[0004] The physicochemical properties of nickel cobalt manganese hydroxide, such as morphology, size, and particle size distribution, directly affect the physicochemical properties of lithium nickel cobalt manganese oxide. Therefore, the preparation of nickel cobalt manganese hydroxide with excellent performance is an important prerequisite for the development of lithium nickel cobalt manganese oxide.
[0005] Under high voltage, the internal resistance of ternary cathode materials increases with the number of cycles, the battery capacity decays quickly, and the cycle performance deteriorates. At the same time, due to the large amount of lithium ions released under high voltage, ternary cathode materials are prone to a series of problems such as poor crystal structure stability, ion mixing, and irreversible phase change.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first purpose of the present invention is to provide a high-voltage precursor material, which has both high tap density and high specific surface area. The positive electrode material prepared by using the precursor material has good cycle performance for batteries under high voltage, low degree of ion mixing, and reduced irreversible phase change; at the same time, the precursor material is doped with element M and has good structural stability.
[0008] The second purpose of the present invention is to provide a method for preparing a high-voltage precursor material, which adopts oxidation and doping methods, and controls a, f, and e to satisfy 1000a-f≥15-e, so as to obtain a precursor material that is loose and porous inside and dense outside, and the precursor material has both high tap density and high specific surface area.
[0009] A third object of the present invention is to provide a positive electrode material which can improve the capacity and cycle performance at high voltage.
[0010] A fourth object of the present invention is to provide a positive electrode sheet, the battery made of which has good cycle performance at high voltage and high capacity.
[0011] The fifth object of the present invention is to provide a lithium ion battery having a faster charge and discharge speed, a high voltage platform and a high battery capacity, and good cycle performance and rate performance.
[0012] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0013] The present invention first provides a high voltage precursor material, the chemical formula of the high voltage precursor material is Ni x Co y Mn z M w (OH)2, wherein 0.1≤y≤0.2, 0.2≤z≤0.4, x+y+z=1, 0.001≤w≤0.015; M is a doping element, and M includes at least one of Mg, Al, Ce, Mo, B and Ta; the tap density of the high voltage precursor material is ≥1.90 g / cm 3 ; The specific surface area of the high voltage precursor material is ≥10m 2 / g.
[0014] Furthermore, the tap density of the high voltage precursor material is ≥2.0 g / cm 3 .
[0015] Furthermore, the specific surface area of the high voltage precursor material is ≥12m 2 / g.
[0016] Furthermore, the median particle size of the high voltage precursor material is 3.5 to 15 μm.
[0017] The present invention further provides a method for preparing the high-voltage precursor material, comprising the following steps: under a first atmosphere, adding a metal mixed salt solution, a complexing agent solution and a precipitant solution to a base liquid to carry out a nucleation reaction; wherein the first atmosphere contains oxygen, and the volume percentage of the oxygen is e%; the metal mixed salt solution includes Ni, Co and Mn elements; after the nucleation reaction is completed, adjusting the reaction atmosphere to a second atmosphere, and adding a doped metal salt solution to the reaction system to carry out a growth reaction; wherein the second atmosphere contains oxygen, and the volume percentage of the oxygen is f%; the doped metal salt solution contains M elements, wherein M includes at least one of Mg, Al, Ce, Mo, B and Ta; the ratio of the molar amount of the M element in the doped metal salt solution to the sum of the molar amounts of the Ni, Co and Mn elements in the metal mixed salt solution is a; and a, f and e satisfy the following relationship: 1000a-f≥15-e.
[0018] Furthermore, the e% is 5% to 15%.
[0019] Furthermore, the f% is less than 10%.
[0020] Furthermore, the a is 0.001 to 0.015.
[0021] Furthermore, during the nucleation reaction, the pH of the reaction system is 11.0 to 12.5.
[0022] Furthermore, during the nucleation reaction, the concentration of aqueous ammonia in the reaction system is 1.5 to 6.0 g / L.
[0023] Furthermore, during the nucleation reaction, the temperature of the reaction system is 40-70°C.
[0024] Furthermore, the pH of the base solution is 11.0-12.5, and the concentration of ammonia water is 1.5-6.0 g / L.
[0025] Furthermore, the nucleation reaction time is 20 to 120 minutes.
[0026] Furthermore, during the growth reaction, the pH of the reaction system is 9.0-11.5.
[0027] Furthermore, during the growth reaction, the ammonia concentration of the reaction system is 2.0 to 4.0 g / L.
[0028] Furthermore, during the growth reaction, the temperature of the reaction system is 40-70°C.
[0029] Furthermore, the growth reaction results in a median particle size of particles in the reaction system of 3.5 to 15 μm.
[0030] Furthermore, the total molar concentration of the metal elements in the metal mixed salt solution is 0.5 to 5 mol / L.
[0031] Furthermore, the complexing agent solution includes at least one of an aqueous ammonia solution, an ammonium carbonate solution, an ammonium nitrate solution, an ammonium chloride solution and ammonium sulfate.
[0032] Furthermore, the molar concentration of the complexing agent solution is 5 to 15 mol / L.
[0033] Furthermore, the precipitant solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution.
[0034] Furthermore, the molar concentration of the precipitant solution is 5 to 20 mol / L.
[0035] Furthermore, the mass concentration of the doped metal salt solution is 2 to 10 g / L.
[0036] Furthermore, after the growth reaction, at least one step of aging, washing, drying, demagnetization and screening is also included.
[0037] The present invention further provides a positive electrode material, which is mainly prepared by sintering a lithium source and the high-voltage precursor material.
[0038] The present invention further provides a positive electrode sheet, comprising the positive electrode material.
[0039] The present invention also provides a lithium ion battery, comprising the positive electrode sheet.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) The high-voltage precursor material provided by the present invention has both high tap density and high specific surface area. Therefore, the positive electrode material prepared by the present invention has a slow capacity decay at high voltage and excellent cycle performance. In addition, due to the advantages of high tap density and high specific surface area, the degree of ion mixing is reduced and irreversible phase change is suppressed. At the same time, by doping the precursor material with a specific type of M element, bulk phase doping can ensure the stability of the structure, thereby suppressing the Jahn-Teller effect, alleviating capacity decay and improving high-temperature cycle stability.
[0042] (2) The high voltage precursor material provided by the present invention also has high capacity.
[0043] (3) The preparation method of the precursor material provided by the present invention adopts a staged oxidation and doping method, and controls a, f, and e to satisfy the relationship 1000a-f≥15-e, so as to obtain a precursor material that is loose and porous inside and dense outside. The precursor material has both high tap density and high specific surface area, breaking through the limitation of the prior art that the tap density and specific surface area cannot be improved simultaneously.
[0044] (4) The preparation method of the precursor material provided by the present invention also has the advantages of simple and controllable operation, less added materials, no introduction of other impurities, low cost, and mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0046] Figure 1 This is a SEM image of the high voltage precursor material prepared in Example 1 provided by the present invention;
[0047] Figure 2 A cross-sectional SEM image of the high voltage precursor material prepared in Example 1 provided by the present invention;
[0048] Figure 3 This is a SEM image of the precursor material prepared in Comparative Example 1 provided by the present invention;
[0049] Figure 4 This is a SEM image of the precursor material prepared in Comparative Example 2 provided by the present invention;
[0050] Figure 5 This is a cross-sectional SEM image of the precursor material prepared in Comparative Example 2 provided by the present invention. DETAILED DESCRIPTION
[0051] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0052] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0053] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0054] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0055] In a first aspect, the present invention provides a doped high-tap high-specific-weight high-voltage precursor material, wherein the chemical formula of the high-voltage precursor material is Ni x Co y Mn z M w (OH)2. Wherein, 0.1≤y≤0.2, 0.2≤z≤0.4, x+y+z=1, 0.001≤w≤0.015. M is a doping element, and M includes at least one of Mg, Al, Ce, Mo, B and Ta, and two, three, four or more of them may also be selected.
[0056] Wherein, y includes but is not limited to any one of 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2 or a range between any two of them; z includes but is not limited to any one of 0.2, 0.23, 0.25, 0.28, 0.3, 0.33, 0.35, 0.38, 0.4 or a range between any two of them; w includes but is not limited to any one of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, 0.011, 0.012, 0.013, 0.014, 0.015 or a range between any two of them.
[0057] The tap density of the high voltage precursor material is ≥1.90 g / cm 3 ; Including but not limited to 1.90g / cm 3 、1.92g / cm 3, 1.93g / cm 3 , 1.95g / cm 3 , 1.97g / cm 3 、1.98g / cm 3 , 2.0g / cm 3 , 2.02g / cm 3 , 2.05g / cm 3 , 2.07g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 Any point value in or any range of values between them.
[0058] The specific surface area of the high voltage precursor material is ≥10m 2 / g; but not limited to 10m 2 / g, 10.3m 2 / g, 10.5m 2 / g, 10.8m 2 / g, 11m 2 / g, 11.2m 2 / g, 11.5m 2 / g, 11.8m 2 / g, 12m 2 / g, 12.3m 2 / g, 12.5m 2 / g, 12.8m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, or a range of values between them.
[0059] The precursor material provided by the present invention has both high tap density and high specific surface area. Therefore, after the positive electrode material prepared therefrom is used to form a battery, the capacity decay is slow under high voltage and has excellent cycle performance. In addition, due to the advantages of both high tap density and high specific surface area, the degree of ion mixing is reduced and irreversible phase change is suppressed.
[0060] At the same time, by doping the precursor material with a specific type of M element, bulk doping can ensure the stability of the structure, thereby inhibiting the Jahn-Teller effect, alleviating capacity attenuation and improving high-temperature cycle stability.
[0061] Furthermore, the doped high-voltage precursor material with both high tap compaction and high specific surface area provided by the present invention is used in a battery, which can also increase the capacity of the battery.
[0062] In some specific embodiments, the tap density of the high voltage precursor material is ≥2.0 g / cm 3The further improvement of the tap density is conducive to further improving the cycle performance of the high-voltage precursor material and the battery prepared therefrom.
[0063] In some specific embodiments, the specific surface area of the high voltage precursor material is ≥12m 2 The further improvement of the specific surface area is conducive to further improving the cycle performance of the high-voltage precursor material and the battery prepared therefrom.
[0064] In some specific embodiments, the median particle size of the high voltage precursor material is 3.5 to 15 μm, including but not limited to any point value of 3.5 μm, 3.8 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 13 μm, and 15 μm, or a range value between any two of them.
[0065] In a second aspect, the present invention provides a method for preparing the high voltage precursor material, which is a coprecipitation reaction, including a nucleation reaction and a growth reaction, and specifically includes the following steps:
[0066] In a first atmosphere, a metal mixed salt solution, a complexing agent solution and a precipitant solution are added to a base solution to perform a nucleation reaction to obtain a crystal nucleus. The first atmosphere contains oxygen, and the volume percentage of the oxygen is e%. The metal mixed salt solution includes Ni, Co and Mn elements.
[0067] It is understood that the molar ratio of Ni, Co and Mn elements in the metal mixed salt solution is x:y:z, wherein 0.1≤y≤0.2, 0.2≤z≤0.4, and x+y+z=1. It can be set as required or according to the chemical formula of the preset high voltage precursor material.
[0068] In some specific implementations, soluble salts of nickel, cobalt and manganese, such as sulfates, chlorides, nitrates, acetates, etc., are selected according to the required molar ratio of nickel, cobalt and manganese elements and mixed with water to prepare a metal mixed salt solution.
[0069] It can be understood that the base solution is mainly formed by mixing and adjusting the complexing agent solution, the precipitating agent solution and water.
[0070] After the nucleation reaction is completed, the reaction atmosphere is adjusted to the second atmosphere (ie, the oxygen content in the reaction system is adjusted), and a doped metal salt solution is added to the reaction system to perform a growth reaction.
[0071] The solid content of the growth reaction is gradually increased through dense concentration treatment until the particle size in the mixed system reaches the target particle size and the coprecipitation reaction is stopped. The gradually increasing solid content can control the growth reaction speed and improve the sphericity of the particles.
[0072] The second atmosphere contains oxygen, and the volume percentage of the oxygen is f%. The doped metal salt solution contains M element, wherein M includes at least one of Mg, Al, Ce, Mo, B and Ta. In the reaction system, the ratio of the molar amount of the M element in the doped metal salt solution to the sum of the molar amounts of Ni, Co and Mn elements in the metal mixed salt solution is a.
[0073] It is understandable that a can be controlled by adjusting the concentration of the doped metal salt solution and the metal mixed salt solution in the reaction system and their flow rate.
[0074] It is understood that the first atmosphere and the second atmosphere may include inert gases in addition to oxygen, such as nitrogen, argon, helium, etc., but not limited thereto. The source of oxygen may also be air. That is, the reaction atmosphere is formed by mixing inert protective gases such as nitrogen, argon, helium, etc. with oxygen and compressed air.
[0075] The a, the f and the e satisfy the following relationship: 1000a-f≥15-e.
[0076] The preparation method of the precursor material provided by the present invention adopts the method of staged oxidation and doping, and controls a, f, and e to satisfy the relationship 1000a-f≥15-e, so as to obtain a precursor material that is loose and porous inside and dense outside. The precursor material has both high tap density and high specific surface area, breaking through the limitation of the prior art that the tap density and specific surface area cannot be improved simultaneously.
[0077] In addition, the preparation method has the advantages of simple and controllable operation, less added materials, no introduction of other impurities, low production cost, and large-scale mass production.
[0078] In some specific embodiments, in order to further improve both the tap density and the specific surface area, the e% is 5% to 15%, including but not limited to any point value of 5%, 6%, 7%, 8%, 9%, 10%, 12%, 13%, 14%, 15% or a range between any two of them.
[0079] In some specific embodiments, in order to further improve both the tap density and the specific surface area, the f% is less than 10%, including but not limited to any point value of 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5% or a range value between any two of them.
[0080] In some specific embodiments, in order to further improve the structural stability, capacity, cycle and other performance of the precursor material, a is 0.001 to 0.015, including but not limited to any point value of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, 0.011, 0.012, 0.013, 0.014, 0.015 or the range value between any two of them.
[0081] In some specific embodiments, during the nucleation reaction, the pH of the reaction system is 11.0-12.5, including but not limited to any point value of 11.0, 11.3, 11.5, 11.7, 12, 12.2, 12.5 or a range of values between any two of them.
[0082] In some specific embodiments, during the nucleation reaction, the ammonia concentration of the reaction system is 1.5-6.0 g / L; including but not limited to any point value of 2.5 g / L, 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L, 5 g / L, 5.5 g / L, 6.0 g / L or a range value between any two of them.
[0083] It is understandable that the pH and ammonia concentration of the reaction system can be controlled by controlling the parallel flow rate or the parallel flow rate of each solution.
[0084] In some specific implementations, stirring is performed during the nucleation reaction, and the stirring speed is controlled to be 250-500 rpm.
[0085] In some specific embodiments, during the nucleation reaction, the temperature of the reaction system is 40-70°C, including but not limited to any point value of 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C or a range value between any two of them.
[0086] Using the above-mentioned pH, ammonia concentration and temperature during the nucleation reaction can obtain a loose inner core, which is beneficial to improving both the tap density and specific surface area of the precursor material.
[0087] In some specific embodiments, the pH of the base solution is 11.0-12.5, including but not limited to any one of 11.0, 11.3, 11.5, 11.7, 12.0, 12.2, 12.5 or a range between any two of them; the concentration of ammonia water in the base solution is 1.5-6.0 g / L; including but not limited to any one of 2.5 g / L, 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L, 5 g / L, 5.5 g / L, 6.0 g / L or a range between any two of them.
[0088] In some specific embodiments, the nucleation reaction time is 20 to 120 min, including but not limited to any point value of 20 min, 30 min, 40 min, 60 min, 80 min, 90 min, 100 min, 120 min or a range value between any two of them.
[0089] In some specific embodiments, the nucleation reaction is performed until the median particle size of the obtained crystal nuclei is 0.5 to 2.0 μm.
[0090] After the nucleation reaction is completed, the obtained crystal nuclei are made to enter the growth stage by changing the pH of the reaction system and the concentration of the complexing agent solution, and the mixed gas of the inert gas and oxygen and / or air is continuously introduced to adjust the reaction atmosphere to the second atmosphere. The metal mixed salt solution, the complexing agent solution, and the precipitant solution are continuously added to the reaction system in parallel, and the doping metal salt solution is added at the same time to control the doping amount a.
[0091] In some specific embodiments, during the growth reaction, the pH of the reaction system is 9.0-11.5, including but not limited to any point value of 9.0, 9.3, 9.5, 9.8, 10.0, 10.3, 10.5, 10.8, 11.0 or a range between any two of them.
[0092] In some specific embodiments, during the growth reaction, the ammonia concentration of the reaction system is 2.0-4.0 g / L; including but not limited to any point value of 2.0 g / L, 2.3 g / L, 2.5 g / L, 2.8 g / L, 3 g / L, 3.2 g / L, 3.5 g / L, 3.7 g / L, 4.0 g / L or a range value between any two of them.
[0093] In some specific embodiments, during the growth reaction, the temperature of the reaction system is 40-70°C, including but not limited to any point value of 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C or a range value between any two of them.
[0094] Using the above pH, ammonia concentration and temperature during the growth reaction can obtain a dense outer layer, which is beneficial to improving both the tap density and specific surface area of the precursor material.
[0095] In some specific implementations, stirring is performed during the growth reaction, and the stirring speed is controlled to be 100-500 rpm (the speed is adjusted according to the particle size during the reaction).
[0096] In some specific embodiments, the median particle size of the particles in the growth reaction to the reaction system is 3.5 to 15 μm, including but not limited to any point value of 3.5 μm, 3.8 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 13 μm, 15 μm or a range value between any two of them.
[0097] In some specific embodiments, the total molar concentration of metal elements in the metal mixed salt solution (the sum of the molar concentrations of Ni, Co, and Mn) is 0.5 to 5 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L or 4 mol / L.
[0098] In some specific embodiments, the complexing agent solution includes at least one of an aqueous ammonia solution, an ammonium carbonate solution, an ammonium nitrate solution, an ammonium chloride solution, and ammonium sulfate.
[0099] In some specific embodiments, the molar concentration of the complexing agent solution is 5 to 15 mol / L;
[0100] For example, 6mol / L, 8mol / L, 10mol / L or 13mol / L.
[0101] In some specific embodiments, the precipitant solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution.
[0102] In some specific embodiments, the molar concentration of the precipitant solution is 5 to 20 mol / L;
[0103] For example, 6mol / L, 8mol / L, 10mol / L, 13mol / L, 15mol / L, 18mol / L or 20mol / L.
[0104] In some specific embodiments, the doped metal salt solution is prepared from a water-soluble salt containing M and water. The water-soluble salt containing M includes but is not limited to at least one or more of sulfates, chlorides, nitrates, acetates, tantalates or molybdates containing M.
[0105] In some specific embodiments, the mass concentration of the doped metal salt solution is 2 to 10 g / L; for example, 3 g / L, 4 g / L, 5 g / L, 6 g / L or 8 g / L.
[0106] In some specific embodiments, after the growth reaction, at least one step of aging, washing, drying, demagnetization and screening is also included; preferably, aging, washing, drying (such as baking), demagnetization and screening are performed in sequence to obtain a high voltage precursor material.
[0107] In some specific embodiments, the aging time is 1 to 20 hours. The purpose of aging is to facilitate the subsequent washing and further formation of crystal particles. After aging, washing equipment such as a centrifuge and a washing machine can be used for washing, and water, ethanol or other solvents that do not dissolve the product and do not react with the product and do not pollute the product are used for washing until the solvent is clear and transparent and the conductivity is less than 10us / cm. After washing, drying equipment such as an oven dryer is used for drying. The drying temperature can be set to 100 to 150°C, and the drying time is 5 to 24 hours. After drying, demagnetization can be performed manually or by demagnetization equipment using a manual permanent magnetic demagnetizer, etc., and a sieve with a mesh size of 300 to 800 is used in the screening step to finally obtain a doped precursor material with high tap density and high specific surface area.
[0108] In a third aspect, the present invention provides a positive electrode material, which is mainly prepared by mixing and sintering a lithium source and the high-voltage precursor material.
[0109] This positive electrode material can effectively improve the first discharge specific capacity and cycle performance of medium nickel ternary batteries at high voltage.
[0110] In some specific embodiments, the lithium source includes but is not limited to one or more of lithium carbonate, lithium oxalate, and lithium hydroxide.
[0111] In some specific implementations, the raw materials are mixed and ground according to a molar ratio of lithium element to high voltage precursor material of 0.9 to 1.2:1, and then sintered.
[0112] In some specific implementations, the sintering temperature is 600-1000° C., the holding time is 5-15 hours, and the sintering is performed in a tubular furnace.
[0113] In a fourth aspect, the present invention provides a positive electrode sheet comprising the positive electrode material.
[0114] The battery made of the positive electrode sheet has good cycle performance under high voltage, high capacity and fast charge and discharge speed.
[0115] Optionally, the positive electrode sheet further includes a conductive agent and a binder, which is not limited in the present invention.
[0116] As an example, the conductive agent includes one or more of graphite, carbon nanotubes, graphene, carbon black, and graphyne, and the binder includes one or more of PVDF (polyvinylidene fluoride), SA (sodium alginate), PVA (polyvinyl alcohol), PMMA (polymethyl methacrylate), HNBR (hydrogenated nitrile rubber), PTFE (polytetrafluoroethylene), and PAA (polyacrylic acid).
[0117] As an example, the mass ratio of the positive electrode material to the conductive agent and the binder can be set to 6-10:0.5-2:1.
[0118] In a fifth aspect, the present invention provides a lithium-ion battery, comprising the positive electrode sheet.
[0119] The lithium-ion battery has a fast charge and discharge speed, a high voltage platform and a high battery capacity, and good cycle performance and rate performance.
[0120] The lithium-ion battery further includes a negative electrode sheet. During the charge and discharge process of the secondary battery, the positive electrode sheet and the negative electrode sheet form a loop. The negative electrode sheet includes lithium, copper, graphite, etc. The lithium-ion battery further includes an electrolyte and a diaphragm stacked between the positive electrode sheet and the negative electrode sheet.
[0121] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0122] Example 1
[0123] This embodiment provides a high voltage precursor material Ni 0.60 Co 0.10 Mn 0.30 Mg 0.010 The preparation method of (OH)2 comprises the following steps:
[0124] According to Ni 0.60 Co 0.10 Mn 0.30 Mg 0.010 The molar ratio of nickel, cobalt and manganese elements in (OH)2 is 60:10:30. Nickel sulfate, cobalt sulfate and manganese sulfate are selected as raw materials and prepared with ultrapure water to prepare a metal mixed salt solution with a total molar concentration of metal elements of 2.0 mol / L; a sodium hydroxide solution with a concentration of 11.0 mol / L is prepared; an ammonia solution with a concentration of 7.5 mol / L is prepared; and a magnesium sulfate solution with a concentration of 5 g / L is prepared.
[0125] Sodium hydroxide solution, ammonia solution and ultrapure water are put into the reaction equipment, and the reaction base liquid is adjusted to pH=12.00-12.05 and ammonia concentration of 2.0-2.5 g / L (the pH and ammonia concentration of the base liquid and the reaction system are difficult to be constant at a specific value and have certain fluctuations, so they are range values). Coprecipitation reaction is carried out: (1) Nucleation reaction stage: The above-prepared metal mixed salt solution, sodium hydroxide solution and ammonia solution are added to the above-prepared base liquid, and the pH of the mixed solution reaction system is controlled to be 12.00-12.05 and the ammonia concentration is 2.0-2.5 g / L by controlling the parallel flow speed or parallel flow rate of each solution. At the same time, the stirring speed is controlled to be 550 rpm and the temperature of the reaction system is 50°C. The oxygen content (i.e., the volume percentage occupied by oxygen) e of the reaction system is 10% by mixing nitrogen and compressed air, and a loose core is obtained. The reaction time of the nucleation reaction stage is 60 min. (2) Growth reaction stage: After the nucleus is formed, the reaction temperature is raised to 60°C, and the flow rate of the metal mixed salt solution, sodium hydroxide solution and ammonia solution is adjusted to make the system pH = 10.60-10.70, and the ammonium concentration is 3.0-4.0 g / L. Then, magnesium sulfate solution is added to make the doping amount a (a is the ratio of the molar amount of the M element in the doped metal salt solution to the sum of the molar amounts of the Ni, Co and Mn elements in the metal mixed salt solution in the reaction system) to 0.010, and at the same time, a mixed gas (a mixture of nitrogen and air) with an oxygen content (i.e., the volume percentage of oxygen) f of 3% is introduced to form a dense outer layer. When the median particle size of the slurry in the reactor reaches 3.8 μm, the feeding is stopped.
[0126] After stopping the feeding, the obtained slurry was aged in the reactor for 2 hours. The aged slurry was washed, dried at 130° C. for 12 hours, passed through a 325-mesh sieve, and demagnetized to obtain the high-voltage precursor material of this embodiment.
[0127] The Mg-doped nickel small particle high tap density and high specific surface area NCM high voltage precursor material prepared in this embodiment has a median particle size of 3.8 μm and a tap density of 1.92 g / cm 3 , with a specific surface area of 12.55m 2 / g, chemical formula is Ni 0.60 Co 0.10 Mn 0.30 Mg 0.010 (OH)2.
[0128] like Figure 1 The figure shows a 10K-fold electron microscope image of the high voltage precursor material prepared in this embodiment. Figure 1 It can be seen that the primary particles of the high voltage precursor material are long and thin, with a smooth surface, good sphericity, and a small amount of pore structure on the surface.
[0129] Figure 2This is a cross-sectional SEM image of the high voltage precursor material prepared in Example 1. It can be seen that the precursor material is loose and porous inside and dense outside.
[0130] Example 2
[0131] This embodiment provides a high voltage precursor material Ni 0.60 Co 0.10 Mn 0.30 Mg 0.008 The preparation method of (OH)2 comprises the following steps:
[0132] According to Ni 0.60 Co 0.10 Mn 0.30 Mg 0.008 The molar ratio of nickel, cobalt and manganese elements in (OH)2 is 60:10:30. Nickel sulfate, cobalt sulfate and manganese sulfate are selected as raw materials and prepared with ultrapure water to prepare a metal mixed salt solution with a total molar concentration of metal elements of 2.0 mol / L; a sodium hydroxide solution with a concentration of 11.0 mol / L is prepared; an ammonia solution with a concentration of 7.5 mol / L is prepared; and a magnesium sulfate solution with a concentration of 5 g / L is prepared.
[0133] Sodium hydroxide solution, ammonia solution and ultrapure water are added to the reaction equipment, and the reaction base liquid is adjusted to pH=11.80-11.90 and ammonia concentration of 1.5-2.5 g / L (the pH and ammonia concentration of the base liquid and the reaction system are difficult to be constant at a specific value, and have certain fluctuations, so they are range values). Coprecipitation reaction is carried out: (1) Nucleation reaction stage: The above-prepared metal mixed salt solution, sodium hydroxide solution and ammonia solution are added to the base liquid together, and the pH of the mixed solution reaction system is controlled to be 11.80-11.90 and the ammonia concentration is 1.5-2.5 g / L by controlling the parallel flow speed or parallel flow rate of each solution. At the same time, the stirring speed is controlled to be 550 rpm and the temperature of the reaction system is 50°C. The oxygen content e of the reaction system is 12% by mixing nitrogen and oxygen to obtain a loose core. The reaction time of the nucleation stage is 60 min. (2) Growth reaction stage: After the nucleus is formed, the reaction temperature is raised to 60°C, and the flow rate of the metal mixed salt solution, sodium hydroxide solution and ammonia solution is adjusted to make the system pH = 11.00-11.10, and the ammonium concentration is 2.5-3.0 g / L. Then, magnesium sulfate solution is added to make the doping amount a 0.008, and at the same time, a mixed gas (a mixture of nitrogen and oxygen) with an oxygen content f of 3% is introduced to form a dense outer layer. When the median particle size of the slurry in the reactor reaches 3.8 μm, the feeding is stopped.
[0134] After stopping the feeding, the obtained slurry was aged in the reactor for 2 hours. The aged slurry was washed, dried at 130° C. for 12 hours, passed through a 325-mesh sieve, and demagnetized to obtain the high-voltage precursor material of this embodiment.
[0135] The Mg-doped nickel small particles with high tap density and high specific surface area NCM precursor material prepared in this embodiment have a median particle size of 3.8 μm and a tap density of 2.07 g / cm 3 , with a specific surface area of 10.34m 2 / g, chemical formula is Ni 0.60 Co 0.10 Mn 0.30 Mg 0.008 (OH)2.
[0136] Example 3
[0137] This embodiment provides a high voltage precursor material Ni 0.60 Co 0.10 Mn 0.30 Mg 0.008 The preparation method of (OH)2 comprises the following steps:
[0138] According to Ni 0.60 Co 0.10 Mn 0.30 Mg 0.008 The molar ratio of nickel, cobalt and manganese elements in (OH)2 is 60:10:30. Nickel sulfate, cobalt sulfate and manganese sulfate are selected as raw materials and prepared with ultrapure water to prepare a metal mixed salt solution with a total molar concentration of metal elements of 3.0 mol / L; a sodium hydroxide solution with a concentration of 8.0 mol / L is prepared; an ammonia solution with a concentration of 8 mol / L is prepared; and a magnesium sulfate solution with a concentration of 4 g / L is prepared.
[0139] Sodium hydroxide solution, ammonia solution and ultrapure water are added to the reaction equipment, and the reaction base liquid is adjusted to pH=11.80-11.90 and ammonia concentration of 3-3.5 g / L (the pH and ammonia concentration of the base liquid and the reaction system are difficult to be constant at a specific value and have certain fluctuations, so they are range values). Coprecipitation reaction is carried out: (1) Nucleation reaction stage: The above-prepared metal mixed salt solution, sodium hydroxide solution and ammonia solution are added to the base liquid together, and the pH of the mixed solution reaction system is controlled to be 11.80-11.90 and the ammonia concentration is 3-3.5 g / L by controlling the parallel flow speed or parallel flow rate of each solution. At the same time, the stirring speed is controlled to 300 rpm and the temperature of the reaction system is 60°C. The oxygen content e of the reaction system is 12% by mixing nitrogen and oxygen to obtain a loose core. The reaction time of the nucleation stage is 40 minutes. (2) Growth reaction stage: After the nucleus is formed, the reaction temperature is raised to 70°C, and the flow rate of the metal mixed salt solution, sodium hydroxide solution and ammonia solution is adjusted to make the system pH = 9.60-9.70, and the ammonium concentration is 2.5-3.0 g / L. Then, magnesium sulfate solution is added to make the doping amount a 0.008, and at the same time, a mixed gas (a mixture of nitrogen and oxygen) with an oxygen content f of 3% is introduced to form a dense outer layer. When the median particle size of the slurry in the reactor reaches 8 μm, the feeding is stopped.
[0140] After stopping the feeding, the obtained slurry was aged in the reactor for 3 hours. The aged slurry was washed, dried at 140° C. for 8 hours, passed through a 325-mesh sieve, and demagnetized to obtain the high-voltage precursor material of this embodiment.
[0141] Example 4
[0142] This embodiment provides a high voltage precursor material Ni 0.60 Co 0.10 Mn 0.30 Mg 0.008 The preparation method of (OH)2 comprises the following steps:
[0143] According to Ni 0.60 Co 0.10 Mn 0.30 Mg 0.008 The molar ratio of nickel, cobalt and manganese elements in (OH)2 is 60:10:30. Nickel sulfate, cobalt sulfate and manganese sulfate are selected as raw materials and prepared with ultrapure water to prepare a metal mixed salt solution with a total molar concentration of metal elements of 4.0 mol / L; a sodium hydroxide solution with a concentration of 15.0 mol / L is prepared; an ammonia solution with a concentration of 10 mol / L is prepared; and a magnesium sulfate solution with a concentration of 7 g / L is prepared.
[0144] Sodium hydroxide solution, ammonia solution and ultrapure water are added to the reaction equipment, and the reaction base liquid is adjusted to pH=11.20-11.30 and ammonia concentration of 2.5-3.0 g / L (the pH and ammonia concentration of the base liquid and the reaction system are difficult to be constant at a specific value and have certain fluctuations, so they are range values). Coprecipitation reaction is carried out: (1) Nucleation reaction stage: The above-prepared metal mixed salt solution, sodium hydroxide solution and ammonia solution are added to the base liquid together, and the pH of the mixed solution reaction system is controlled to be 11.20-11.30 and the ammonia concentration is 2.5-3 g / L by controlling the parallel flow speed or parallel flow rate of each solution. At the same time, the stirring speed is controlled to 400 rpm and the temperature of the reaction system is 45°C. The oxygen content e of the reaction system is 12% by mixing nitrogen and oxygen to obtain a loose core. The reaction time of the nucleation stage is 120 min. (2) Growth reaction stage: After the nucleus is formed, the reaction temperature is raised to 55°C, and the flow rate of the metal mixed salt solution, sodium hydroxide solution and ammonia solution is adjusted to make the system pH = 10.00-10.10, and the ammonium concentration is 2.5-3.0 g / L. Then, magnesium sulfate solution is added to make the doping amount a 0.008, and at the same time, a mixed gas (a mixture of nitrogen and oxygen) with an oxygen content f of 3% is introduced to form a dense outer layer. When the median particle size of the slurry in the reactor reaches 10 μm, the feeding is stopped.
[0145] After stopping the feeding, the obtained slurry was aged in the reactor for 5 hours. The aged slurry was washed, dried at 120° C. for 15 hours, passed through a 325-mesh sieve, and demagnetized to obtain the high-voltage precursor material of this embodiment.
[0146] Example 5
[0147] The preparation method of the high voltage precursor material provided in this embodiment is substantially the same as that in Embodiment 1, except that the oxygen content e of the reaction system in the nucleation reaction stage is replaced with 8%.
[0148] Example 6
[0149] The preparation method of the high voltage precursor material provided in this embodiment is basically the same as that in Embodiment 1, except that the oxygen content f of the reaction system in the growth reaction stage is replaced with 1%.
[0150] Example 7
[0151] The preparation method of the high voltage precursor material provided in this embodiment is basically the same as that in Embodiment 1, except that the oxygen content e of the reaction system in the nucleation reaction stage is replaced with 13%, and the oxygen content f of the reaction system in the growth reaction stage is replaced with 8%.
[0152] Example 8
[0153] Referring to the preparation method of Example 1, a high voltage precursor material Ni 0.60 Co 0.10 Mn 0.30 Mg 0.015 (OH)2, the difference between the preparation method in this embodiment and that in embodiment 1 is that the doping amount a in the growth reaction stage is controlled to be 0.015.
[0154] Example 9
[0155] Referring to the preparation method of Example 1, a high voltage precursor material Ni 0.60 Co 0.10 Mn 0.30 Mg 0.002 (OH)2, the difference between the preparation method in this embodiment and that in Embodiment 1 is that the oxygen content e of the reaction system in the nucleation reaction stage is replaced with 15%, the oxygen content f of the reaction system in the growth reaction stage is replaced with 2%, and the doping amount a in the growth reaction stage is 0.002.
[0156] Example 10
[0157] Referring to the preparation method of Example 1, a high voltage precursor material Ni 0.60 Co 0.20 Mn 0.20 Al 0.010 The preparation method of (OH)2, the difference between this embodiment and the preparation method in embodiment 1 is: according to Ni 0.60 Co 0.20 Mn 0.20 Al 0.010 The molar ratio of nickel, cobalt and manganese elements in (OH)2 is 60:20:20. Nickel chloride, cobalt chloride and manganese chloride are selected as raw materials and prepared with ultrapure water to prepare a metal mixed salt solution with a total molar concentration of metal elements of 2.0 mol / L, and the magnesium sulfate solution is replaced by an aluminum chloride solution of equal concentration.
[0158] Embodiment 11
[0159] Referring to the preparation method of Example 1, a high voltage precursor material Ni 0.50 Co 0.10 Mn 0.40 Ce 0.010 The preparation method of (OH)2, the difference between this embodiment and the preparation method in embodiment 1 is: according to Ni 0.50 Co 0.10 Mn 0.40 Ce 0.010The molar ratio of nickel, cobalt and manganese elements in (OH)2 is 50:10:40. Nickel nitrate, cobalt nitrate and manganese nitrate are selected as raw materials and prepared with ultrapure water to prepare a metal mixed salt solution with a total molar concentration of metal elements of 2.0 mol / L, and the magnesium sulfate solution is replaced with a cerium nitrate solution of equal concentration.
[0160] Example 12
[0161] Referring to the preparation method of Example 1, a high voltage precursor material Ni 0.60 Co 0.10 Mn 0.30 B 0.010 The preparation method of (OH)2, the difference between this embodiment and the preparation method in embodiment 1 is: the magnesium sulfate solution is replaced by a sodium borate solution of equal concentration.
[0162] Comparative Example 1
[0163] Referring to the preparation method of Example 1, the precursor material Ni 0.60 Co 0.10 Mn 0.30 (OH)2, the difference between the preparation method in this comparative example and that in Example 1 is that no magnesium sulfate solution is added, and the oxygen content f of the reaction system in the growth reaction stage is 0% (i.e., no oxygen is introduced). That is, the precursor material prepared in this comparative example is not doped with Mg.
[0164] like Figure 3 The 10K-fold electron microscope image of the precursor material prepared in this comparative example is shown. Figure 3 It can be seen that the primary particles of the precursor material are in the shape of thick strips, which are thick and curled, and have appropriate pores on the surface.
[0165] Comparative Example 2
[0166] The preparation method of the precursor material provided in this comparative example is basically the same as that of Example 1, except that the oxygen content e of the reaction system in the nucleation reaction stage is replaced with 6%, and the oxygen content f of the reaction system in the growth reaction stage is replaced with 10%.
[0167] like Figure 4 The 10K-fold electron microscope image of the precursor material prepared in this comparative example is shown. Figure 4 It can be seen that the primary particles of the precursor material are fine needle-shaped, and the surface of the particles has a rich pore structure. Figure 5 This is a cross-sectional SEM image of the precursor material prepared in Comparative Example 2.
[0168] Comparative Example 3
[0169] The preparation method of the precursor material provided in this comparative example is basically the same as that of Example 1, except that the oxygen content e of the reaction system in the nucleation reaction stage is replaced with 2%, and the oxygen content f of the reaction system in the growth reaction stage is 0% (i.e., no oxygen is introduced).
[0170] Comparative Example 4
[0171] Referring to the preparation method of Example 1, the precursor material Ni 0.60 Co 0.10 Mn 0.30 (OH)2, the difference between the preparation method in this comparative example and that in Example 1 is that no magnesium sulfate solution is added, and the oxygen content e of the reaction system in the nucleation reaction stage is replaced by 6%, and the oxygen content f of the reaction system in the growth reaction stage is replaced by 10%.
[0172] Comparative Example 5
[0173] The preparation method of the precursor material provided in this comparative example is basically the same as that of Example 1, except that the oxygen content e of the reaction system in the nucleation reaction stage is replaced with 5%, and the oxygen content f of the reaction system in the growth reaction stage is replaced with 5%.
[0174] In each embodiment and each comparative example, the oxygen content e of the reaction system in the nucleation reaction stage, the oxygen content f of the reaction system in the growth reaction stage, the doping amount a in the growth reaction stage, and whether 1000a-f≥15-e is satisfied are shown in Table 1.
[0175] Table 1e, f, a and whether 1000a-f≥15-e is satisfied
[0176] Group e f a Does it satisfy 1000a-f≥15-e? Example 1 10 3 0.010 7>5, satisfied Example 2 12 3 0.008 5>3, satisfied Example 3 12 3 0.008 5>3, satisfied Example 4 12 3 0.008 5>3, satisfied Example 5 8 3 0.010 7=7, satisfied Example 6 10 1 0.010 9>5, satisfied Example 7 13 8 0.010 2=2, which satisfies Example 8 10 3 0.015 12>5, satisfied Example 9 15 2 0.002 0=0, satisfied Example 10 10 3 0.010 7>5, satisfied Embodiment 11 10 3 0.010 7>5, satisfied Example 12 10 3 0.010 7>5, satisfied Comparative Example 1 10 0 / 0<5, not satisfied Comparative Example 2 6 10 0.010 0<9, not satisfied Comparative Example 3 2 0 0.010 10<13, not satisfied Comparative Example 4 6 10 / / Comparative Example 5 5 5 0.010 5<10, not satisfied
[0177] The tap density and specific surface area of the high voltage precursor materials prepared in each embodiment and the precursor materials prepared in each comparative example are shown in Table 2, respectively.
[0178] Furthermore, the high voltage precursor material prepared in each embodiment and the precursor material prepared in each comparative example were mixed with lithium carbonate (lithium source) at a molar ratio of lithium element to precursor material = 1.08:1, and ground in a mortar to fully mix the two; after grinding, it was vacuum dried, then heated to 950°C in an oxygen atmosphere for 10 hours, and then cooled at a rate of 2°C / min to obtain a positive electrode material after cooling. The positive electrode materials prepared by the above methods were pulped, coated, rolled and dried to form positive electrode sheets, and lithium sheets were used as negative electrodes to assemble button batteries. The composition of the positive electrode sheet is: the mass ratio of positive electrode active material, acetylene black, and polyvinylidene fluoride (PVDF) = 80:10:10, and the positive electrode sheet uses aluminum foil as the current collector; the electrolyte composition is: 1 mol / L LiPF6 ethylene carbonate (EC) + dimethyl carbonate (DMC) + diethyl carbonate (DEC) solution (volume ratio is 1:1:1). After that, the electrochemical performance of each button cell was tested. The electrochemical performance test was carried out using a blue electric test system. The charge and discharge voltage was 2.8~4.5V, the test temperature was 25℃, and the first discharge capacity at a current density of 0.1C and the cycle performance after 100 cycles were tested. The results are shown in Table 2 below.
[0179] Table 2 Tap density and specific surface area of precursor materials, battery electrical performance test results
[0180]
[0181]
[0182] It can be seen from Table 2 that the high-voltage precursor materials prepared in each embodiment have both high tap density and high specific surface area, and each embodiment is doped. Therefore, the first discharge specific capacity and the capacity retention rate after 100 cycles of the batteries assembled in each embodiment reach a relatively high level, and the first discharge specific capacity even reaches the level of high nickel.
[0183] Among them, the ionic radius of the doping element Mg is 2+ With Li + The ionic radius is similar, Mg 2+ Can enter the crystal structure of NCM materials, occupy the Li site, and the electrochemically inactive Mg 2+ It becomes the pillar of the Li layer and can stabilize the layered structure in the high lithium removal state. In addition, it can effectively inhibit the Li + / Ni 2+ Cation mixing (other doping elements also have the same effect).
[0184] In Comparative Example 1, although the conditions for high specific surface area are met, its tap density is low because the degree of oxidation in the growth reaction stage is weakened and Mg is not doped. Its first discharge specific capacity and capacity retention rate after 100 cycles are not as good as those in Example 1.
[0185] Although comparative example 2 was doped, it did not meet 1000a-f≥15-e and the oxygen content of the reaction system in the growth reaction stage was high, resulting in a low tap density. Therefore, its cycle performance was weakened and was only 78.7%.
[0186] Comparative Example 3 is the opposite of Comparative Example 2. Although the tap density is high, the specific surface area is low, resulting in that it cannot fully react with lithium during the high-temperature solid phase reaction, and there is too much residual alkali, which causes serious particle adhesion, thereby reducing the specific capacity and capacity retention rate.
[0187] The first discharge specific capacity and capacity retention rate after 100 cycles of comparative example 4 further decreased, which further verified that high tap density and high specific surface area can improve the capacity and cycle performance of lithium-ion batteries, and doping on this basis can further improve the capacity and cycle performance of lithium-ion batteries.
[0188] Comparative Example 5 does not satisfy 1000a-f≥15-e, and the oxygen content in the nucleation reaction stage is the same as that in the growth reaction stage, resulting in a loose and porous structure inside and a dense structure outside. Therefore, its battery capacity and cycle performance are also reduced.
[0189] In summary, the high-voltage precursor material provided by the present invention has both high tap density and high specific surface area, and is doped with element M. The positive electrode material prepared therefrom is assembled into a battery, which has high capacity and excellent cycle performance under high voltage, and the degree of ion mixing is low, and the irreversible phase change is reduced.
[0190] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A high voltage precursor material, characterized in that: The chemical formula of the high voltage precursor material is Ni x Co y Mn z M w (OH)2, wherein 0.1≤y≤0.2, 0.2≤z≤0.4, x+y+z=1, 0.001≤w≤0.015; M is a doping element, and M includes at least one of Mg, Al, Ce, Mo, B and Ta; The tap density of the high voltage precursor material is ≥1.90 g / cm 3 ; The specific surface area of the high voltage precursor material is ≥10m 2 / g.
2. The high voltage precursor material according to claim 1, characterized in that: At least one of the following conditions is met: (1) The tap density of the high voltage precursor material is ≥ 2.0 g / cm 3 ; (2) The specific surface area of the high voltage precursor material is ≥ 12 m 2 / g; (3) The median particle size of the high voltage precursor material is 3.5 to 15 μm.
3. The method for preparing a high voltage precursor material according to claim 1 or 2, characterized in that: The steps include: Under a first atmosphere, a metal mixed salt solution, a complexing agent solution and a precipitant solution are added to a base solution to perform a nucleation reaction; wherein the first atmosphere contains oxygen, and the volume percentage of the oxygen is e%; the metal mixed salt solution includes Ni, Co and Mn elements; After the nucleation reaction is completed, the reaction atmosphere is adjusted to a second atmosphere, and a doped metal salt solution is added to the reaction system to perform a growth reaction; wherein the second atmosphere contains oxygen, and the volume percentage of the oxygen is f%; the doped metal salt solution contains an M element, wherein M includes at least one of Mg, Al, Ce, Mo, B and Ta; the ratio of the molar amount of the M element in the doped metal salt solution to the sum of the molar amounts of the Ni, Co and Mn elements in the metal mixed salt solution is a; The a, the f and the e satisfy the following relationship: 1000a-f≥15-e.
4. The method for preparing a high voltage precursor material according to claim 3, characterized in that: At least one of the following conditions is met: (1) The e% is 5% to 15%; (2) the f% is less than 10%; (3) a is 0.001 to 0.
015.
5. The method for preparing the high voltage precursor material according to claim 3, characterized in that: At least one of the following conditions is met: (1) During the nucleation reaction, the pH of the reaction system is 11.0 to 12.5; (2) During the nucleation reaction, the concentration of aqueous ammonia in the reaction system is 1.5 to 6.0 g / L; (3) During the nucleation reaction, the temperature of the reaction system is 40 to 70° C.; (4) The pH of the base solution is 11.0 to 12.5, and the concentration of ammonia water is 1.5 to 6.0 g / L; (5) The nucleation reaction time is 20 to 120 minutes.
6. The method for preparing a high voltage precursor material according to claim 3, characterized in that: At least one of the following conditions is met: (1) During the growth reaction, the pH of the reaction system is 9.0 to 11.5; (2) During the growth reaction, the concentration of ammonia in the reaction system is 2.0 to 4.0 g / L; (3) During the growth reaction, the temperature of the reaction system is 40 to 70° C.; (4) The growth reaction results in a median particle size of particles in the reaction system of 3.5 to 15 μm.
7. The method for preparing a high voltage precursor material according to claim 3, characterized in that: At least one of the following conditions is met: (1) The total molar concentration of the metal elements in the metal mixed salt solution is 0.5 to 5 mol / L; (2) the complexing agent solution comprises at least one of an aqueous ammonia solution, an ammonium carbonate solution, an ammonium nitrate solution, an ammonium chloride solution and ammonium sulfate; (3) The molar concentration of the complexing agent solution is 5 to 15 mol / L; (4) the precipitant solution comprises at least one of a sodium hydroxide solution and a potassium hydroxide solution; (5) The molar concentration of the precipitant solution is 5 to 20 mol / L; (6) The mass concentration of the doped metal salt solution is 2 to 10 g / L; (7) After the growth reaction, the method further comprises at least one of aging, washing, drying, demagnetizing and screening.
8. A positive electrode material, characterized in that It is mainly prepared by sintering a lithium source and the high voltage precursor material as claimed in claim 1 or 2.
9. A positive electrode sheet, characterized in that: Comprising the positive electrode material as claimed in claim 8.
10. A lithium ion battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 9.